The Relevance of Certainty and Fairness to Notary Honorarium Values in the Notary Position Law - Wangsa, I Gusti Agung Wisnu Satria; Suwitra, I Made; Utama, I Wayan Kartika Jaya (Journal of Law, Politic and Humanities, 2026)
This study discusses the regulation of notary fees in Article 36 of the Notary Law (UUJN) in relation to the principles of legal certainty and justice. The problem arises because this provision regulates the maximum fee, but does not provide clear parameters regarding economic and sociological values, nor does it regulate the minimum fee. This study uses a normative legal research method with a regulatory approach and a conceptual approach using primary, secondary, and tertiary legal materials. The results of the study show that the regulation of notary fees provides legal legitimacy for notaries to receive compensation for the legal services they provide and aims to provide legal protection for notaries and the public. However, the ambiguity of the norms in this provision has the potential to cause differences in interpretation and tariff competition between notaries. Therefore, the determination of notary fees needs to be done proportionally by taking into account legal provisions, professional codes of ethics, and social conditions.